Utilizing Transformers for Interactive Chatbot Development (Journal of Computational Intelligence and Robotics, 2024)
Transformers, a novel architecture introduced by Vaswani et al. in "Attention is All You Need" (2017), have revolutionized natural language processing (NLP) by effectively using attention mechanisms to process and generate human language. This paper explores the implementation of a chatbot using the transformer model, specifically focusing on the practical aspects of tokenization, model selection, and generation of responses. The paper outlines the methods used, presents results from various model configurations, and provides an analysis of the chatbot's performance. Improvements and future directions are also discussed.